Forecasting Migration and Integration Trends Using Digital Demography~– A Case Study of Emigration Flows from Croatia to Austria and Germany - Tado Jurić (Comparative Southeast European Studies, 2022)
This paper was created as a result of the observed instability of external emigration data from Croatian official data in comparison to data from the statistical offices of the European Union (Eurostat) and Germany (DESTATIS). In this study, the author presents a descriptive analysis of alternative data sources (big data), which could be useful for determining emigration flows from Croatia to Austria and Germany, as well as for estimating and forecasting. The second goal of this paper is to show that this approach can be useful for assessing the degree of cultural assimilation/integration of Croatian emigrants using the tools of Google Trends and Facebook Analytics. To estimate the model, linear regression was used to measure the correlation between the number of searches ( x ) and the number of moves ( y ) evidenced by the official statistics.
Keywords: 330; digital demography; migration; Croatia; Germany; Austria